Incidence of Shock in Patients Treated in an Emergency Department after Sustaining a Road Traffic Injury - Eiamla-or, Petcharat; Thosingha, Orapan; Danaidutsadeekul, Suporn; Viwatwongkasem, Chukiat; Hegadoren, Kathy (Pacific Rim International Journal of Nursing Research, 2020)
Road traffic injuries in Thailand are the major cause of death and disabilities in young adults. The presence of shock plays an important role in clinical outcomes.This cross-sectional study aimed to determine the incidence of shock and to identify factors predicting the presence of shock on discharge from the emergency department in patients sustaining moderate to serious road traffic injuries in Thailand. Five hundred and three patients (N=503),who scored at least 16 on the Injury Severity Score on admission to an emergency department were recruited.Population and contextual variables were collected from patients’ medical records and patients and triage nurses’ interviews. Two standardized tools were used to measure the severity of injury and the presence of shock.Data analyses included descriptive statistics, univariate analysis and multivariate logistical regression. Results indicated that the majority of patients were males, wearing no safety devices and had consumed alcohol prior to driving their motorcycle. The incidence of shock on discharge from the emergency department to the operating room, intensive care unit or general ward was 35%. Transport time, injury severity, shock on arrival and time spent in the emergency department all made significant contributions to whether patients were in shock on discharge from the emergency department. Our findings suggest that emergency nurses should perform routine ongoing calculation of Modified Shock Index scores for monitoring the moderately to severely injured.Further studies examining the superiority of the Modified Shock Index over cardiorespiratory parameters alone could provide evidence to consider the inclusion of this Index into best practice guidelines.